2020
DOI: 10.1108/lodj-07-2019-0329
|View full text |Cite
|
Sign up to set email alerts
|

Responsible leadership and triple-bottom-line performance—do corporate reputation and innovation mediate this relationship?

Abstract: PurposeDrawing on stakeholder theory and contingency theory, this study empirically investigates the relationship between responsible leadership (RL) and each dimension of triple-bottom-line (TBL) performance. Moreover, we tested the mediating effect of corporate reputation (CR) and innovation between RL and TBL performance.Design/methodology/approachPerceptual data were collected from 227 senior-level Pakistani managers using a questionnaire survey. Structural equation modeling (SEM) was used to test the dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 70 publications
1
31
2
Order By: Relevance
“…RL is positively associated with corporate reputation [86], corporate sustainability performance, and financial [85,86], environmental, and social performance [85]. The positive relations between RL and all units of the triple bottom line suggest that RL does not induce trade-offs between financial and environmental performance.…”
Section: Meso-levelmentioning
confidence: 94%
See 2 more Smart Citations
“…RL is positively associated with corporate reputation [86], corporate sustainability performance, and financial [85,86], environmental, and social performance [85]. The positive relations between RL and all units of the triple bottom line suggest that RL does not induce trade-offs between financial and environmental performance.…”
Section: Meso-levelmentioning
confidence: 94%
“…In addition to psychological frameworks, some of the studies took on business theoretical perspectives. Considering the close theoretical tie between RL and stakeholder theory it is no surprise that several studies applied this theoretical framework [74,83,85], which includes a strategic perspective lacking from social psychological approaches. Upper echelons theory was also applied in the empirical studies [60] and centred on leaders' personal experiences, attitudes and values and how it influences decision-making within the boundaries of organizational decision latitude.…”
Section: Theoretical Framework In Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Asian context, specific research investigates RL's effect on micro, meso and macro-level outcomes like unethical pro-organizational behaviour, talent retention, organizational citizenship behaviour, environmental performance, job performance and pandemic management (Yasin et al, 2020;Javed et al, 2020a;Afsar et al, 2020;Zhao and Zhou, 2019;Haque et al, 2019aHaque et al, , 2019bHan et al, 2019;Mehta et al, 2020;Lin et al, 2020). While exploring the Western developed notion of RL in the Asian context, Koh et al (2018) observed that Asian leaders possessed values and traits accordant with the Western concept of RL.…”
Section: Peeking Through the Asian Context Of Pakistanmentioning
confidence: 99%
“…While exploring the Western developed notion of RL in the Asian context, Koh et al (2018) observed that Asian leaders possessed values and traits accordant with the Western concept of RL. Further, the construct of RL has already been studied in Pakistani context (Javed et al, 2020a(Javed et al, , 2020bAfsar et al, 2020) which addresses and dispels the apprehensions regarding the contextual factors.…”
Section: Peeking Through the Asian Context Of Pakistanmentioning
confidence: 99%